Climate change impacts on groundwater hydrology – where are the main uncertainties and can they be reduced?. Issue 13 (2nd October 2016) - Refsgaard, J.C.; Sonnenborg, T.O.; Butts, M.B.; Christensen, J.H.; Christensen, S.; Drews, M.; Jensen, K.H.; Jørgensen, F.; Jørgensen, L.F.; Larsen, M.A.D.; Rasmussen, S.H.; Seaby, L.P.; et al.
ABSTRACT: This paper assesses how various sources of uncertainty propagate through the uncertainty cascade from emission scenarios through climate models and hydrological models to impacts, with a particular focus on groundwater aspects from a number of coordinated studies in Denmark. Our results are similar to those from surface water studies showing that climate model uncertainty dominates the results for projections of climate change impacts on streamflow and groundwater heads. However, we found uncertainties related to geological conceptualization and hydrological model discretization to be dominant for projections of well field capture zones, while the climate model uncertainty here is of minor importance. How to reduce the uncertainties on climate change impact projections related to groundwater is discussed, with an emphasis on the potential for reducing climate model biases through the use of fully coupled climate–hydrology models.Editor D. Koutsoyiannis;Associate editor not assigned